Assessing the performance of genetic risk score for stratifying risk of post-sepsis cardiovascular complications - McElligott, Brian; Shi, Zhuqing; Rifkin, Andrew S.; Wei, Jun; Zheng, S. Lilly; Helfand, Brian T.; Woo, Jonathan S. H.; Xu, Jianfeng (Frontiers in Cardiovascular Medicine, 2023)
Background Patients with sepsis are at increased risk for cardiovascular complications, including myocardial infarction (MI), ischemic stroke (IS), and venous thromboembolism (VTE). Our objective is to assess whether genetic risk score (GRS) can differentiate risk for these complications. Methods A population-based prospective cohort of 483,177 subjects, derived from the UK Biobank, was followed for diagnosis of sepsis and its complications (MI, IS, and VTE) after the study recruitment. GRS for each complication was calculated based on established risk-associated single nucleotide polymorphisms (SNPs). Time to incident MI, IS, and VTE was compared between subjects with or without sepsis and GRS risk groups using Kaplan–Meier log-rank test and Cox-regression analysis. Results During an average of 12.6 years of follow-up, 10,757 (2.23%) developed sepsis. Patients with sepsis had an overall higher risk than non-sepsis subjects for each complication, but the risk differed by time after a sepsis diagnosis; exceedingly high in short-term (0–30 days), considerably high in mid-term (31 days to 2 years), and reduced in long-term (>2 years). Furthermore, in White subjects, GRS was a significant predictor of complications, independent of sepsis and other risk factors. For example, GRSMI further differentiated their risk in patients with sepsis; 3.49, 4.73, and 9.03% in those with low- (<0.5), intermediate- (0.5–1.99), high- GRSMI (≥2.0), Ptrend < 0.001. Conclusion Risk for post-sepsis cardiovascular complications differed considerably by time after a sepsis diagnosis and GRS. These findings, if confirmed in other ancestry-specific populations, may guide personalized management for preventing post-sepsis cardiovascular complications.